Assessment of watershed ecosystem health in red-soil region: A case study in Nanxi River - YOU Shixue; LI Peng; CAI Jingbo; HUANG Zhou; DENG Jinsong; ZHOU Mengmeng; HU Shuigen (浙江大学学报. 农业与生命科学版, 2018)
In order to provide scientific supports for watershed sustainable development, operation and management, Nanxi River was selected as a typical red-soil region, and ecosystem health assessment methodology and pressure analysis combining remote sensing (RS), geographic information system (GIS) and multi-index were applied. The ecosystem health assessment was classified into two categories: water area and terrestrial area, and the indices were divided into six sections including habitat structure, aquatic organisms, ecological pressure of water area and ecological patterns, ecological function, ecological pressure of terrestrial area, which consisted of 16 sub-indicators. The results showed that the health condition of the study area was good, and only the aquatic organisms and ecological function were in ordinary condition. Among them, 83.3% of sub-basins were in good condition, while the others were in ordinary condition, and all of them were located in the downstream areas. Human disturbance was the major reason of the degradation of watershed ecosystem health, such as rapid growth of urban land areas, excessive livestock breeding and fishing. In order to improve the health conditions, more attention should be paid to adjusting the scope of the conservation areas, controlling pollution from point and nonpoint sources as well as protecting the biodiversity. The proposed assessment methodology can comprehensively indicate the health condition of Nanxi River. This case study could make a contribution to guiding the watershed management in ecologically fragile areas, and ensuring the water ecological health of the basin and its downriver.